2021
DOI: 10.1016/j.isci.2021.102423
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein interaction inhibitor of SRPKs alters the splicing isoforms of VEGF and inhibits angiogenesis

Abstract: Structure-based design of a protein-protein interaction inhibitor of SRPK PPI inhibitor of SRPK inhibits angiogenesis by switching VEGF splicing SRPK-specific substrate docking groove serves as promising drug target site Combination of PPI and ATP-competitive inhibitors of SRPK enhances antiangiogenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…S5 A ). This could have important implications on the splicing of various gene transcripts and the consequent production of alternative protein isoforms, including, for example, vascular endothelial growth factor ( 67 ). Finally, a third interesting interaction suggested by Mechismo involves R264 of SAM synthase (MAT2A); this modification is located at the interface between the two subunits forming the active dimer of the enzyme, where it contacts E57 of the other MAT2A monomer, ATP, and metal ions serving as cofactors ( supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5 A ). This could have important implications on the splicing of various gene transcripts and the consequent production of alternative protein isoforms, including, for example, vascular endothelial growth factor ( 67 ). Finally, a third interesting interaction suggested by Mechismo involves R264 of SAM synthase (MAT2A); this modification is located at the interface between the two subunits forming the active dimer of the enzyme, where it contacts E57 of the other MAT2A monomer, ATP, and metal ions serving as cofactors ( supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that an R-methyl-site is involved in SRSF1–SRPK1 interaction is also intriguing, as Ngo et al. ( 67 ) have recently shown that disrupting this interaction promotes alternative splicing events triggering the translation of a vascular endothelial growth factor isoform that displays antiangiogenic properties. In this study, the authors used a PPI inhibitor to modulate SRSF1–SRPK1 interaction; along this line, based on our result, it will be interesting to assess whether pharmacological modulation of PRMTs can elicit the same functional effect.…”
Section: Discussionmentioning
confidence: 99%
“…LIN28 affects angiogenesis by regulating the expression level of let-7d ( 116 ). In breast cancer, SRPK1 can mediate SRSF1 phosphorylation and promote angiogenesis by regulating VEGF premRNA splicing to generate proangiogenic isoforms ( 117 ). Regulation of the mRNA half-life plays an important role in breast cancer.…”
Section: Function Of Rbps In Breast Cancermentioning
confidence: 99%
“…Interestingly, the use of inhibitors of SRPK1, the kinase responsible for SRSF1 activation, has been recently proposed as powerful antiangiogenic strategy to be used for the treatment of various pathological conditions, included cancer. Inhibition of SRPK1, through the blocking of SRSF1 phosphorylation and activity, leads to the induction of VEGF XXX b isoforms and, consequently, significantly reduces the angiogenic potential of targeted cells 16–18 …”
Section: Regulation Of Vegfa Expressionmentioning
confidence: 99%